Effects of Using a Portable Rotary Rice Weeder on Yield in the North Eastern Regions’ Rice Transplanting Field - Mongkol Kwangwaropas (Agriculture and Natural Resources, 1990)
A Study in basic effect of using newly designed push type rotary rice weeders on yield in transplanting rice fields was conducted in the North Eastern provinces. It was shown that besides destroying weeds, the growth of rice in weeded blocks was also stimulated and the yield was significantly different from the non – weeded blocks. On the average, weeded block yields’ is higher than the non weeded blocks’ from 85.44 to 29.84 kilograms per rai.